2021
DOI: 10.1038/s41598-021-94020-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of ascorbic acid combined exposure on Imidacloprid-induced oxidative stress and genotoxicity in Nile tilapia

Abstract: Imidacloprid (Imid), a systemic neonicotinoid insecticide, is broadly used worldwide. It is reported to contaminate aquatic systems. This study was proposed to evaluate oxidative stress and genotoxicity of Imid on Nile tilapia (Oreochromis niloticus) and the protective effect of ascorbic acid (Asc). O. niloticus juveniles (30.4 ± 9.3 g, 11.9 ± 1.3 cm) were divided into six groups (n = 10/replicate). For 21 days, two groups were exposed to sub-lethal concentrations of Imid (8.75 ppm, 1/20 of 72 h-LC50 and 17.5 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 77 publications
0
8
0
1
Order By: Relevance
“…For instance, paraquat (1,1′-dimethyl-4,4′-bipyridinium dichloride), a non-selective herbicide, at non-cytotoxic concentrations, induces oxidative DNA damage in HepG2 cells [ 12 ]. Imidacloprid, a neonicotinoid insecticide, induces oxidative stress and DNA damage on non-target organisms, namely various fish species such as Danio rerio (zebrafish) [ 13 ], Prochilodus lineatus [ 14 ], and Oreochromis niloticus (Nile tilapia) [ 15 ], affecting various organs (e.g., gills, kidney, brain, liver), as assessed by the levels of stress defence enzyme activity and by comet assay [ 13 , 14 , 15 ]. Imidacloprid was also reported to induce oxidative stress and inflammation in the hepatic and central nervous system of rats [ 16 ] and was associated with multiple neurobehavioral aberrations in adolescent and adult rats [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, paraquat (1,1′-dimethyl-4,4′-bipyridinium dichloride), a non-selective herbicide, at non-cytotoxic concentrations, induces oxidative DNA damage in HepG2 cells [ 12 ]. Imidacloprid, a neonicotinoid insecticide, induces oxidative stress and DNA damage on non-target organisms, namely various fish species such as Danio rerio (zebrafish) [ 13 ], Prochilodus lineatus [ 14 ], and Oreochromis niloticus (Nile tilapia) [ 15 ], affecting various organs (e.g., gills, kidney, brain, liver), as assessed by the levels of stress defence enzyme activity and by comet assay [ 13 , 14 , 15 ]. Imidacloprid was also reported to induce oxidative stress and inflammation in the hepatic and central nervous system of rats [ 16 ] and was associated with multiple neurobehavioral aberrations in adolescent and adult rats [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the MN frequency in the erythrocytes of P. lineatus did not increase significantly, the ENAs frequency increased significantly as a result of aluminum exposure (Galindo et al, 2010). However, as in the erythrocytes of C. carpio individuals exposed to metal(oid) mixtures, it was reported that the frequency of both MN and ENA was also increased in erythrocyte cells of Nil tilapia exposed to ascorbic acid (ElGarawani et al, 2021). The different types of ENAs were determined such as blebbed nuclei (B), binucleated cell (BN), kidney-shaped nuclei (KS), lobed nuclei (L), and notched nuclei (N) in the erythrocyte cells of C. carpio in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, studies confirming the harmful effects on fish of IMI and THI, two NEO insecticides frequently detected in aquatic environments, involve pure parent compounds or pesticide formulations, not their metabolites. It is known that by generating DNA damage and inducing oxidative stress, they damage tissues of Danio rerio , Oreochromis niloticus , Prochilodus lineatus 22 , 23 , 27 , 30 – 33 .…”
Section: Introductionmentioning
confidence: 99%